ANALISIS PENGARUH PRICE EARNINGS RATIO (PER), NON PERFORMING LOAN (NPL), BANK SIZE, DEBT TO EQUITY RATIO (DER), KEPEMILIKAN INSTITUSIONAL TERHADAP KEPERCAYAAN INVESTOR (STUDI KASUS PADA PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BEI PERIODE 2016 2020) - Ichsan Arya Nugraha; Muhamad Syaichu (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to examine the effect of Price Earning Ratio (PER), Non Performing Loan (NPL), Bank Size, Debt Equity Ratio (DER) and Ownership Institutional to Investors Trust in Banking Companies Conventional listed on the Indonesia Stock Exchange. Investor Confidence measured by using Market Capitalization (MC). The Independent Variable used in this study is the Price Earning Ratio (PER), Non- Performing Loan (NPL), Bank Size, Debt Equity Ratio (DER) and Ownership Institutional. The sample used in this study is a banking company Conventional listed on the Indonesia Stock Exchange (IDX) for a period of 2016-2020. The number of samples as many as 7 companies taken by the method target sample. The analytical method used is panel data regression with Moderate Regression Analysis (MRA) with the Eviews:10 program which previously passed the classical assumption test. Fix effect was chosen as the best model. The results of the study show that the Price Earning Ratio (PER) has an effect no significant positive on Investor Confidence. Non-performing Loans (NPL) no significant positive effect on Investor Confidence. Bank Size significant positive effect on Investor Confidence. Debt Equity The ratio (DER) has significant positive effect on Investor Confidence. While Institutional Ownership has no significant negative effect to Investor Confidence.